Society of Flavor Chemists newsletter, October 1973 - Society of Flavor Chemists (1973)
October 1973 issue of the Society of Flavor Chemists newsletter.
Keywords: Newsletters; Flavoring essences; Flavoring essences industry; Flavor; Food additives; Food additives industry; Society of Flavor Chemists; Minutes (Records)